Development of a sample exchange system for irradiations in the BH-3 channel of the IEA-R1 reactor at IPEN - Marcio Luis de Paula; Maurício Moralles; Frederico Antônio Genezini; Paulo de Tarso Dalledone Siqueira; Iberê Souza Ribeiro Junior; Iremar Alves da Silva Júnior (Brazilian Journal of Radiation Sciences)
This work was developed with the aim of improving the current sample exchange system of the BH-3 irradiation channel of the IEA-R1 reactor at IPEN. The instrument's operating concept will provide a better use of the irradiation space as well as greater safety and confidence to the operator. The development of the system involved 3D modeling, sizing, construction and non-destructive testing of the various parts, and analysis of neutron-induced activation of the materials most exposed to the beam. A programmable logic controller (PLC) was implemented for the system’s control inside a dedicated electrical panel that was built with materials compatible with the location. The system was designed to support samples weighing up to 15 kg. Bench tests were carried out and showed that the system performs the necessary functions to accurately position samples in three locations: outside the biological shield, at the irradiation channel and at the decay waiting station. The implementation of this instrument will contribute to the application of the ALARA principle in the operator activities at the BH-3 irradiation channel.